2000
DOI: 10.1002/1529-0131(200001)43:1<184::aid-anr23>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules in the development of inflammatory infiltrates in giant cell arteritis: Inflammation-induced angiogenesis as the preferential site of leukocyte-endothelial cell interactions

Abstract: JOSÉ HERNA´NDEZHERNA´HERNA´NDEZ-RODRI´GUEZRODRI´RODRI´GUEZ, JORDI ESPARZA, ALVARO URBANO-MA´RQUEZMA´MA´RQUEZ, and JOSEP M. GRAU Objective. To investigate the expression pattern of adhesion molecules involved in leukocyte-endothelial cell interactions in giant cell arteritis (GCA). Methods. Immunohistochemical analysis was performed on frozen temporal artery sections from 32 patients with biopsy-proven GCA and from 12 control patients with other diseases. Adhesion molecules identified were intercellular adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 50 publications
(49 reference statements)
5
70
0
1
Order By: Relevance
“…13 Moreover, neovascularization is more remarkable in patients with a strong systemic acute-phase response 13 who, as we have also shown, are stronger producers of IL-6. 6,9 In addition to its compensatory function, angiogenesis has a proinflammatory role in large and medium-sized vessel vasculitis because newly formed vessels are the main site at which adhesion molecules for leukocytes are expressed 31 and the main sites through which leukocytes invade the vessel wall, as suggested by the transmigratory phenotype of microvessel-surrounding leukocytes. 31,32 We have shown that patients with a strong systemic inflammatory response who have elevated IL-6 production require higher and longer corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…13 Moreover, neovascularization is more remarkable in patients with a strong systemic acute-phase response 13 who, as we have also shown, are stronger producers of IL-6. 6,9 In addition to its compensatory function, angiogenesis has a proinflammatory role in large and medium-sized vessel vasculitis because newly formed vessels are the main site at which adhesion molecules for leukocytes are expressed 31 and the main sites through which leukocytes invade the vessel wall, as suggested by the transmigratory phenotype of microvessel-surrounding leukocytes. 31,32 We have shown that patients with a strong systemic inflammatory response who have elevated IL-6 production require higher and longer corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 80%
“…6,9 In addition to its compensatory function, angiogenesis has a proinflammatory role in large and medium-sized vessel vasculitis because newly formed vessels are the main site at which adhesion molecules for leukocytes are expressed 31 and the main sites through which leukocytes invade the vessel wall, as suggested by the transmigratory phenotype of microvessel-surrounding leukocytes. 31,32 We have shown that patients with a strong systemic inflammatory response who have elevated IL-6 production require higher and longer corticosteroid treatment. 6,9 IL-6 -induced angiogenesis may then contribute to disease perpetuation, given the proinflammatory effects of inflammationinduced angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Vasa vasorum ingrowth and neovascularization extension into the inner third of the media are associated with inflammation in LVV (23). Angiogenesis has a proinflammatory role in LVV because newly formed vessels are the main site at which adhesion molecules for leukocytes are expressed and the main sites through which leukocytes invade the vessel wall (24,25). Therefore, the visualization of contrast microbubbles through the thickened artery wall was construed as a potential sign of inflammation and consequently a marker of disease activity.…”
Section: Discussionmentioning
confidence: 93%
“…Concentric intimal hyperplasia is an important underlying pathologic lesion in GCA. 249 Clinical presentation varies from fever of unknown origin to constitutional symptoms. Arterial lesions may be widespread and the variable expression of GCA can be analyzed according to the anatomical pattern of the arteries affected.…”
Section: Giant Cell Arteritismentioning
confidence: 99%